Comparison of Plasma-Polymerized Thin Films Deposited from 2-Methyl-2-oxazoline and 2-Ethyl-2-oxazoline: I Film Properties - St'ahel, Pavel; Mazánková, Věra; Prokeš, Lubomír; Buršíková, Vilma; Stupavská, Monika; Lehocký, Marián; Pištěková, Hana; Ozaltin, Kadir; Trunec, David (International journal of molecular sciences, 2023)
Poly(2-oxazoline) is a promising new class of polymeric materials due to their antibiofouling properties and good biocompatibility. Poly(2-oxazoline) coatings can be deposited on different substrates via plasma polymerization, which can be more advantageous than other coating methods. The aim of this study is to deposit poly(2-oxazoline) coatings using a surface dielectric barrier discharge burning in nitrogen at atmospheric pressure using 2-methyl-2-oxazoline and 2-ethyl-2-oxazoline vapours as monomers and compare the film properties. For the comparison, the antibacterial and cytocompatibility tests were peformed according to ISO norms. The antibacterial tests showed that all the deposited films were highly active against Staphylococcus aureus and Escherichia coli bacteria. The chemical composition of the films was studied using FTIR and XPS, and the film surface's properties were studied using AFM and surface energy measurement. The cytocompatibility tests showed good cytocompatibility of all the deposited films. However, the films deposited from 2-methyl-2-oxazoline exhibit better cytocompatibility. This difference can be explained by the different chemical compositions and surface morphologies of the films deposited from different monomers.
Keywords: Oxazoles; antibiofouling; Escherichia coli; oxazoly; plasma polymer; polymerizace; poly(2-oxazoline); antibakteriální látky; Polymerization; Anti-Bacterial Agents